Tourism Management Strategies to Address Poverty and Unemployment in Support of Economic Growth and State Resilience (Journal Evaluation in Education (JEE), 2025)
Purpose of the Study: This study explores the strategic role of the tourism sector in reducing poverty and unemployment through local economic empowerment, particularly in underdeveloped and border regions of Indonesia. It underscores the importance of a multi-stakeholder collaboration—involving government, private sector, and communities—to address regional disparities, promote inclusive growth, and ensure long-term socio-economic sustainability.Methodology: The research adopts a descriptive-analytic method utilizing secondary data obtained from the Central Statistics Agency (BPS), the Ministry of Finance, and relevant literature. Through comparative data analysis and trend observation, the study evaluates the tourism sector’s impact on socio-economic indicators.Main Findings: The findings reveal that the tourism sector significantly contributes to poverty alleviation and employment creation, particularly through the development of nature- and culture-based tourism. A reduction in poverty from 9.71% in 2021 to 9.54% in 2022 suggests that empowerment initiatives are having a positive impact. However, regional disparities remain prominent, especially in Maluku and Papua, indicating the need for region-specific policies. The synergy among stakeholders plays a crucial role in fostering inclusive and sustainable growth.Novelty/Originality of the Study: This research offers a novel integrative framework positioning tourism not only as an economic driver but also as a tool for inclusive development, cultural preservation, and environmental sustainability. Unlike conventional studies focusing solely on economic growth, this study emphasizes the transformative power of tourism as a pillar of resilience-building and long-term poverty reduction in marginalized and remote areas, making it a critical component of national development policy.
Keywords: Economic Growth; Management Strategies; Poverty; Tourism; Unemployment